Evaluation of intravenous magnesium sulphate on postoperative pain after spinal anesthesia - Subodh S Kamtikar; Sangamesh B Kunakeri (Asian Pacific Journal of Health Sciences, 2015)
The major goal in postoperative pain management is to minimize the dose of medications and lessen side effects, while still providing adequate analgesia. Effective post-operative analgesia may facilitate recovery and decrease morbidity in surgical patients. Magnesium sulphate (MgSO4), a NMDA receptors antagonist, has been tried to control peri-operative pain by modifying the pain mechanism. The present study was conducted to determine efficiency and safety of preventive intravenous MgSO4 to postoperative pain relief and analgesic requirement after spinal anesthesia. This was a open label randomized study conducted in a tertiary care hospital in South India, from March 2013 to September 2013. The study was approved by institutional ethics committee and informed consent was taken from the subjects. The patients were randomized to receive either magnesium sulphate 50 mg/kg in 250 ml of isotonic sodium chloride solution IV (Group MG) or same volume of isotonic sodium chloride solution (Group NS). Pain at rest was evaluated using a 0-10 cm visual analogue scale at emergence from anesthesia and 2, 4, 8, 16 and 24 hrs after surgery. Rescue analgesia was provided in the form of diclofenac 75mg intramuscularly. The dosage and timing of analgesia was recorded immediately after consciousness, 2, 4, 8, 16 and 24 after operation. Results on continuous measurements are presented on Mean ± SD and results on categorical measurements are presented in Number (%). Repeated measures ANOVA were used to compare measurements over time. P˂0.05 was considered statistically significant. The results of the present study showed that infusion of MgSO4 during operation under spinal anesthesia reduced postoperative pain and analgesic consumption. Hemodynamic parameters of both groups were also comparable and no patient developed hypotension or bradycardia in both groups.